Decision criteria and intelligent decision method for tunnel excavation scheme selection considering carbon emissions - Xia, Zhenzhao; Mao, Jingyin; Chen, Guangyao; Wu, Daguo; He, Yao (Frontiers in Environmental Science, 2022)
The construction process of tunnels is accompanied by high resource consumption and non-negligible greenhouse gas emissions. Reducing the carbon emissions of this process is an issue that should be considered in the decision-making stage. For tunnel construction using the drill-and-blast process, selecting a reasonable excavation scheme is a feasible measure to reduce carbon emissions. This paper proposes an evaluation index system that takes into account the stability of the tunnel construction process and the reasonable assessment of carbon emission levels; for various scenarios with different focus on stability requirements, this paper uses theoretical deductions to filter out the key indicators that should be used as assessment items; for the determination of carbon emission assessment indicators, this paper is guided by the life cycle theory, and in the determined calculation boundary, the reference of previous projects and expert opinions are selected as the item source to fill the unfavorable situation in which the carbon emissions of different excavation schemes cannot be accurately calculated due to the lack of bills of quantities in the engineering decision stage. The paper also proposes an intelligent decision method based on a support vector machine to better complete the task of calculating and ranking the utility of excavation schemes in order to adapt the proposed multi-factor parallel evaluation system. Finally, the proposed decision indicator system and decision method were applied to the selection of the excavation scheme in the engineering case, and reasonable and realistic scoring results were obtained.